For f(x) = 3x^2 + 2x - 1, identify the rule for g(x) = f(x + 1) - 6 and it's graph.
1 answer:
2x2 + x −#6 _____________
x2 − 1
∙ x
__
2 + 2x + 1
x 2 − 4
Rewrite as multiplication.
(2x − 3)(x + 2) __
(x + 1)(x − 1) ∙ (x + 1)(x + 1) __ (x + 2)(x − 2) Factor the numerator and denominator.
(2x − 3)(x + 2)(x + 1)(x + 1) ___ (x + 1)(x − 1)(x + 2)(x − 2) Multiply numerators and denominators.
(2x − 3)(x + 2)(x + 1)(x + 1) ___ (x + 1)(x − 1)(x + 2)(x − 2) Cancel common factors to simplify.
(2x − 3)(x + 1) __ (x − 1)(x − 2)
You might be interested in
The area of the triangle with vertices
is
.
Inserting numerical values, the are of the triangle with vertices (0, 0), (6, 2), (4, 8) is
![\Delta = \frac{1}{2}\left|\begin{array}{ccc}1&0&0\\1&6&2\\1&4&8\end{array}\right |\\ \Delta = 0.5(48-8)\\ \Delta = 20 \;square\; units](https://tex.z-dn.net/?f=%5CDelta%20%3D%20%5Cfrac%7B1%7D%7B2%7D%5Cleft%7C%5Cbegin%7Barray%7D%7Bccc%7D1%260%260%5C%5C1%266%262%5C%5C1%264%268%5Cend%7Barray%7D%5Cright%20%7C%5C%5C%0A%5CDelta%20%3D%200.5%2848-8%29%5C%5C%0A%5CDelta%20%3D%2020%20%5C%3Bsquare%5C%3B%20units)
Step-by-step explanation:
y=-3+5x
substitute y into equation 2
3x-8y=24
3x-8(-3+5x)=24
3x+24-40x=24
x=0
y=-3+5(0)
y=-3
(x,y)=(0,3)
Answer:
Obtuse
D)Triangle
D)An acute angle <90 degrees
Step-by-step explanation:
The answer to your question is C.